ANALISIS OTORISASI PENGGUNAAN KEKUATAN BERSENJATA OLEH EUNAVFOR MED DI LAUT MEDITERANIA TERKAIT PENYELUNDUPAN IMIGRAN BERDASARKAN UNSCR 2240, UNCLOS 1982, DAN SMUGGLING PROTOCOL 2000 - Natalia A Rizki Asti (BELLI AC PACIS, 2020)
This research aims to examine the use of forceauthorization of EUNAVFOR MED in Mediterranean Sea regarding the migrant smuggling according to UNSCR 2240, UNCLOS 1982, and Smuggling Protocol 2000. This study is a normative legal research. The type of approach used is the legislative approach and the conceptual approach. The legal material of this study includes primary and secondary legal materials using library research techniques. The analysis technique uses syllogistic methods through deductive thinking patterns. The results of the study indicate that EUNAVFOR MED’s operation is a lawful use of force and migrant smuggling is a threat towards international peace and security which requires authorization to use armed force by UNSCR 2240. EUNAVFOR MED will retain the right to carry out their operations based on those three legal bases